THE IMPACT OF GLOBAL CLIMATE CHANGE ON THE DISTRIBUTION AND POPULATION DYNAMICS OF LEPIDOPTERANS: THE CASE OF THE MULBERRY MOTH (GLYPHODES PYLOALIS WALKER, 1859) (Scientific journal of the Fergana State University, 2025)
This article analyzes the distribution patterns of Lepidopterans in the context of global climate change, focusing on the mulberry moth in the Fergana Valley as a case study. Over the past 22 years, climatic anomalies characterized by sharp fluctuations in minimum and maximum temperatures have increased in the study region. Long-term studies conducted in mulberry plantations revealed that seasonal environmental changes significantly influence the population dynamics of the mulberry moth. Notably, sharp cold snaps during the winters of 2002, 2008, and 2014, as well as the springs of 2015 and 2021, caused a marked decline in population density in subsequent seasons. Conversely, extreme drought conditions during the summer of 2022 and prolonged high-temperature periods highlighted the potential of these factors to limit the development rate of the mulberry moth. These findings underscore the necessity of devising adaptive strategies to manage Lepidopteran pests amidst ongoing global climate changes.